PEMODELAN ARIMA UNTUK PERAMALAN PERMINTAAN EKSPOR KARET DI PT. HOK TONG JAMBI - SIMANJUNTAK, CAROLINA; SYAFMEN, WARDI; Z, GUSMANELY (E-Jurnal Matematika, 2024)
Rubber is one of the most important agricultural commodities for Indonesia and Internationally. The foreign exchange earnings obtained from rubber are quite supportive, and even Indonesia has excelled in controlling the world's rubber products. PT. Hok Tong Jambi is one of the companies that produces crumb rubber (Crumb Rubber) which will be exported. PT. Hok Tong Jambi produces crumb rubber only based on consumer demand so there is no product inventory in the warehouse. From these problems, it is necessary to forecast the number of future export requests so that the company can estimate the amount of raw materials needed and prepare product inventories. The forecasting method used is the ARIMA method because the data on the amount of rubber exports is a time series data type, by reading the ACF and PACF plots to predict the time series data. The purpose of this study is to obtain the best ARIMA model that will be used for forecasting demand for rubber exports and to get the results of forecasting the amount of demand for rubber exports in January - December 2020. The data used is data on the number of rubber exports from January 2016 - December 2020. The results of this research are: In this study, the ARIMA (1,0,1) or ARMA (1,1) models were obtained with the mathematical equation . And the results of the prediction of the amount of demand for rubber exports with this model tend to decrease from January to December 2021.